Muhammad as a heresiarch in the opinion of Christian authors to John of Damascus - Żelazny, Jan Witold (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The article is devoted to the image of Muhammad as a heresiarch in the opinion of Christian authors (to 8th c.)